Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Diabetes Melitus pada Masyarakat di Kelurahan Pahandut Palangka Raya: The Effect of Health Education on the Level of Knowledge about Diabetes Mellitus in the Community in Pahandut Village, Palangka Raya - Carolina, Putria (Jurnal Surya Medika (JSM), 2018)
Diabetes Mellitus (DM) is a syndrome caused by an imbalance between demands and supply of insulin, this disease is a chronic systemic and multifactorial disease that is excised with hyperglycemia and hyperlipidemia. Symptoms that arise are due to lack of insulin secretion or insulin associated with microvascular and macrovascular disorders, neuropathic disorders and dermopathic lesions. This study aims to determine the effect of health education on the level of knowledge about diabetes mellitus in the community in Pahandut Village, Palangka Raya. This study used a pre-experimental design with one group pre-test and post-test design approach. Sampling in this study used purposive sampling technique and obtained a sample of 30 respondents in Pahandut, Palangka Raya. Data collection used a measuring instrument in the form of a questionnaire, the treatment used was health education, data were analyzed using the non-parametric statistical test of the Wilcoxon Sign Ranks Test. The level of knowledge before health education was conducted in the community in Pahandut Palangka Raya Village, it was known that out of 30 respondents there were 20 respondents (67%) with less knowledge, 8 respondents (26%) who had sufficient knowledge and 2 respondents (7%) who had good knowledge. The level of knowledge after being given health education revealed that out of 30 respondents, there were no respondents (0%) who lack knowledge, 8 respondents (27%) were knowledgeable enough and 22 respondents (73%) were well-informed. The results of the analysis through statistical tests were obtained Sig. (2-tailed) 0,000 which means smaller than p-value 0.05, so that the results obtained <p-value (0.000 <0.05). So it can be concluded that there is an effect of health education on the level of knowledge about diabetes mellitus in the community in Pahandut Palangka Raya.